Agile Group Holdings Limited (Hoover's Company Records, 2025)
Agile Property Holdings is nimbly building residential communities across mainland China. It develops large-scale residential projects in mostly townhouse-style and multi-story towers. It boasts about 120 properties in 40 cities throughout China, many of which are concentrated in the Pearl River Delta region. Altogether, Agile Property owns a land bank of 43 million sq. meters (5 million of which is developed). The company operates eight property management companies and 23 branches. It's engaged in property management and interior design. In 2007, it expanded to the hotel business after building two luxury properties in the Guangdong Province.